DESAIN DAN PENGEMBANGAN SERTA PEMANFAATAN TEKNOLOGI PEMBELAJARAN PADA PENDIDIKAN DASAR - Fulusia Nurmawati; Agung Prihatmojo; Afroh Nailil Hikmah; Azila Rahma Kamila (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
The purpose of this service is to carry out the Tri Dharma of Higher Education activities, one of which is community service activities, providing education to educators in increasing knowledge about developing learning technology designs, and as a consideration for carrying out sustainable community service activities. The role of learning technology in learning design is complex and varied. Overall, learning technology plays a role as the main driver in designing learning that is more adaptive, interactive and effective. Although, technology has the potential to enrich learning experiences, it also raises concerns regarding the digital divide, teacher capabilities, and curriculum alignment. A balanced approach to instructional design, which combines the power of technology with the wisdom of traditional teaching methods, is essential to achieving effective learning outcomes. The use of learning media to be effective requires the application of an appropriate learning approach. The solution to partner problems, namely one approach that is suitable for the society 5.0 era, is the STEM approach. The basis for implementing community service activities. The results of this service are the success of the target number of service participants, achievement of service goals, achievement of planned material targets, participants' ability to master the material, participants' ability to practice the technology that has been delivered by the service, collaboration between the campus and partners, achievement in improving quality digital-based assessment, achievement in increasing understanding of digital-based media innovation.